2012
DOI: 10.1111/j.1476-5381.2012.02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Central hypotensive effects of neuropeptide Y are modulated by endothelial nitric oxide synthase after activation by ribosomal protein S6 kinase

Abstract: BACKGROUND AND PURPOSENeuropeptide Y (NPY) is a 36-amino acid polypeptide found abundantly in the central and peripheral nervous systems. NPY exerts a potent depressor effect via the activation of both Y1 and Y2 receptors in the nucleus tractus solitarii (NTS) of rats. However, the precise mechanisms involved in this NPY-mediated action remained unclear. EXPERIMENTAL APPROACHEffects of a selective antagonist of Y1 receptors, a PKC inhibitor, a PI3 kinase inhibitor, a NOS inhibitor, an endothelial NOS (eNOS)-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…This finding, to some extent, was consistent with our previous observations that TXL decreased myocardial infarct size induced by I/R through the protein kinase A (PKA)/eNOS pathway (Cheng et al, 2009;Li et al, 2010;Li X. D. et al, 2013). It was demonstrated that p70s6k activation by neuropeptide Y or cysteine-rich, angiogenic inducer 61, promoted eNOS phosphorylation in endothelial cells and led to blood vessel relaxation (Cheng et al, 2012;Hwang et al, 2015). Moreover, two other studies showed that increased p70s6k1 phosphorylation facilitated PKA expression and enhanced its activity in tissues (Soulard et al, 2010;Jiang et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…This finding, to some extent, was consistent with our previous observations that TXL decreased myocardial infarct size induced by I/R through the protein kinase A (PKA)/eNOS pathway (Cheng et al, 2009;Li et al, 2010;Li X. D. et al, 2013). It was demonstrated that p70s6k activation by neuropeptide Y or cysteine-rich, angiogenic inducer 61, promoted eNOS phosphorylation in endothelial cells and led to blood vessel relaxation (Cheng et al, 2012;Hwang et al, 2015). Moreover, two other studies showed that increased p70s6k1 phosphorylation facilitated PKA expression and enhanced its activity in tissues (Soulard et al, 2010;Jiang et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…NPY can regulate blood pressure, and the activation of adrenaline, by coupling to the NPY Y1 receptor. In transgenic rodents, over-expression of the NPY gene attenuated the elevation of blood pressure after central Nitric Oxide Synthase (NOS) inhibition administration; the injection of a selective Y1 receptor antagonist, BIBP3226, was shown to reverse this phenomenon centrally [131]. In mice, the specific deletion of the gene encoding NPY Y1 receptor results in changes in adrenergic activity, as well as enhanced biosynthesis and secretion of catecholamine [132].…”
Section: The Characteristics Of Human Npy Receptorsmentioning
confidence: 99%
“…In mice, the specific deletion of the gene encoding NPY Y1 receptor results in changes in adrenergic activity, as well as enhanced biosynthesis and secretion of catecholamine [132]. Peripherally, NPY activates the NPY Y1 receptor receptor and modulates vasoconstrictor or vasopressor responses [133], while centrally, these effects may be the total opposite, and are usually anti-hypertensive [131]. …”
Section: The Characteristics Of Human Npy Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…NPY concentration is increased by 300% following 10 min of cold exposure and remains elevated following removal of the stimulus (20, 34). Additionally, NPY increases Rho-kinase activity (7) which could contribute to the present findings.…”
Section: Discussionmentioning
confidence: 52%